Hubungan Lama Operasi Dengan Tingkat Kejadian Post Operative Nausea And Vomiting (PONV) Dan Shivering Pada Pasien Post Operasi Dengan General Anesthesia - Malikal Bulqis, Putri; Marsaid; Bachtiar , Arief; Supono, Supono (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: To identify therelationship between the length os surgery and teh incidence of post operative nausea and vomiting and shivering in post operativepatiens with general anesthesia. Methods: This article is uses quantitative methods, cross-sectional research design. The research population was post-operative patients with general anesthesia in the recovery room at Karsa Husada Batu Hospital. The research sample size was 67 respondents, using the G*Power application. Correlation Statistical tests use Spearman Rank Correlation Results: The statistical test results show that there is a relationship between the length of operation and the incidence of PONV with a p value (0.001 < 0.05) and there is a relationship between the length of operation and the incidence of shivering with a p value (0.001 < 0.05). Conclusion: The relationship between the length of the operation and the incidence of post-operative nausea, vomiting and shivering shows a significant relationship because the duration of the operation also influences the amount of anesthetic drug given to the patient, as well as increasing the duration of the patient's exposure to the cold temperature of the operating room